Efektivitas Jalur Litigasi dan Jalur Non Litigasi Dalam Penyelesaian Sengketa Batas Laut Indonesia Berdasarkan Unclos 1982 - Adhisukmawati, I Gusti Ayu Kade Harry; Yasa, Made Maharta (Kertha Wicara : Journal Ilmu Hukum; Vol 9 No 12 (2020), 2020)
This study aims to examine and discuss the factors that cause Indonesian maritime boundary disputes and the effectiveness of maritime boundary dispute resolution through ITLOS. The author uses normative legal research methods carried out through an approach to legislation and an approach to cases. A dispute or border dispute between countries, islands, and the sea is a dispute that can be resolved through the role of international law by an international court. Disputes related to maritime boundaries are still frequent, for example disputes in the Malacca Strait between Malaysia and Indonesia, disputes in the Natuna Sea area between Indonesia and Vietnam, disputes over the sea boundaries of the EEZ (Exclusive Economic Zone), disputes in the South China Sea, and other maritime boundary disputes. The existence of conflict in a relationship between countries is caused by a claim unilaterally. This can occur due to the incomplete negotiation between countries, one party (state) committing violations, unclear sea boundaries, and others. UNCLOS 1982 is a Convention from the United Nations with an international scope that can be applied and only applies to countries that have ratified it. There are two routes in resolving maritime boundary disputes, namely through the litigation route and through the non-litigation route, ITLOS is the final solution for the litigation route in resolving maritime boundary disputes. Dispute resolution through litigation is more effective than dispute resolution through non-litigation in resolving maritime boundary disputes in Indonesia.   Key Words: Settlement of Disputes, Sea Border Disputes, UNCLOS 1982